A new species of Platepistoma Rathbun, 1906 (Decapoda: Brachyura: Cancridae) from deep water off South Africa - Davie, Peter J. F.; Ng, Peter K. L. (Zootaxa, 2012)
Platepistoma seani sp. nov. is described from deep water off KwaZulu-Natal Province, South Africa. It can be separatedfrom its nearest relative, Platepistoma guezei (Crosnier, 1976), by its thicker setal covering that completely hides the an-terolateral teeth from dorsal view, less well defined carapace regions, more spinous anterolateral and posterolateral cara-pace margins, sparser but more prominent dorsal carapace spines, more prominent spines on the carpus of the cheliped, and a relatively narrower male telson.